Exploring Self-Efficacy Profiles and Their Influence on Undergraduate Students' Geometry Problem-Solving Processes: A Qualitative Case Study - Jainuddin, Jainuddin; Asih, Endang Cahya Mulyaning; Khatami, Muhammad (Mosharafa: Jurnal Pendidikan Matematika, 2026)
Pemecahan masalah geometri menuntut integrasi antara kemampuan kognitif dan aspek afektif, khususnya efikasi diri. Penelitian ini bertujuan mengidentifikasi profil efikasi diri mahasiswa pendidikan matematika serta menganalisis pengaruhnya terhadap proses pemecahan masalah geometri berdasarkan tahapan Polya. Menggunakan desain studi kasus kualitatif, penelitian ini melibatkan 33 mahasiswa. Data dikumpulkan melalui skala efikasi diri, tes geometri berbasis empat tahap Polya, dan wawancara semi-terstruktur dengan subjek yang merepresentasikan tingkat efikasi diri tinggi, sedang, dan rendah. Hasil penelitian mengungkap tiga profil berbeda: mahasiswa dengan efikasi diri tinggi mampu menunjukkan pemahaman mendalam hingga evaluasi reflektif; mahasiswa dengan efikasi diri sedang mampu melaksanakan prosedur namun tidak stabil pada tahap perencanaan dan evaluasi; sedangkan mahasiswa dengan efikasi diri rendah kesulitan dalam merumuskan strategi dan verifikasi hasil. Temuan ini menegaskan bahwa efikasi diri berpengaruh signifikan terhadap kualitas pemecahan masalah geometri, sehingga perlu diintegrasikan dalam perancangan pembelajaran matematika yang komprehensif. Geometric problem-solving demands the integration of cognitive abilities and affective readiness, notably self-efficacy. This study aims to identify the self-efficacy profiles of mathematics education students and analyze their influence on the geometric problem-solving process based on Polya’s stages. Employing a qualitative case study design, the research involved 33 students. Data were collected through a self-efficacy scale, geometric problem-solving tests structured according to Polya’s four stages, and semi-structured interviews with subjects representing high, moderate, and low self-efficacy levels. The findings reveal three distinct profiles: students with high self-efficacy demonstrate deep understanding followed by reflective evaluation; those with moderate self-efficacy execute procedures correctly but show instability during the planning and evaluation stages; while students with low self-efficacy struggle with strategy formulation and result verification. These findings underscore that self-efficacy significantly influences the quality of geometric problem-solving, highlighting the necessity of integrating affective factors into the design of comprehensive mathematics instruction.